Comparative assessment of single-donor plateletpheresis by Haemonetics(®) MCS(®) plus and Trima Accel(®) - Baruah, Sukanya (Wolters Kluwer - Medknow, 2020)

(untitled) (Asian J Transfus Sci)
BACKGROUND: Single-donor platelets (SDPs) prepared by sophisticated automated equipment offer several advantages over random-donor platelets and are being increasingly used to support thrombocytopenic patients. Different apheresis machines working on the principle of centrifugation are being used worldwide to collect platelets. This retrospective study was done to compare plateletpheresis on two automated cell seperators – Haemonetics(®) MCS(®) Plus and Trima Accel(®). MATERIALS AND METHODS: Data for 100 single-donor plateletpheresis procedures, fifty on each machine, were retrospectively collected and analyzed. Donor characteristics were analyzed by Student's t-test and no significant difference was found between the two groups. The parameters compared between the two machines were yield, collection efficiency, blood volume processed, procedure time, acid-citrate-dextrose (ACD) used, leukodepletion achieved, quality control of the products, and adverse donor reactions. RESULTS: Platelet yield (3.054 ± 0.14 vs. 3.120 ± 0.25), quality control of the platelets, leukodepletion achieved, and donor safety were comparable in both the machines. The blood volume processed (2230.74 ± 227.01 vs. 2452.90 ± 318.61), ACD used during procedure (265.48 ± 43.21 vs. 298.10 ± 53.32), procedural time (55.92 ± 13.00 vs. 68.86 ± 12.64), and the postprocedural decrease in donor count in Trima Accel(®) (183.10 ± 23.99 vs. 161.44 ± 63.47) were significantly less than those in Haemonetics(®) MCS(®) Plus. The median collection efficiency of Trima Accel(®) was found to be greater than Haemonetics(®) MCS(®) Plus (0.000649 vs. 0.000608, P = 0.020). CONCLUSION: Both Trima Accel(®) and Haemonetics(®) MCS(®) Plus can collect SDPs safely and efficiently. Trima Accel(®) has higher collection efficiency and reduced incidence of citrate-related adverse effects. It also has better potential to optimize productivity due to decreased procedural time.